2021
DOI: 10.12998/wjcc.v9.i31.9500
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of the COVID-19 pandemic on Chinese population: An online survey

Abstract: BACKGROUND The ongoing coronavirus disease 2019 (COVID-19) pandemic infiltrates every aspect of our life, including the psychological impact. China has experienced the first wave of this epidemic, and it is now affecting the global population. AIM This study aimed to investigate the prevalence and associated factors of post-traumatic stress disorder (PTSD) among the general Chinese population. METHODS A detailed questionnaire, comprising of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Prior studies demonstrated both short-and long-term psychological effects of pandemics/epidemics including increased post-traumatic stress symptoms, anxiety, depression, helplessness, and risky behaviors (107)(108)(109)(110)(111)(112)(113). The overall rates of depression and anxiety are higher during COVID-19 than prior 16 UNESCO.…”
Section: Role Of the Covid-19 Pandemicmentioning
confidence: 99%
“…Prior studies demonstrated both short-and long-term psychological effects of pandemics/epidemics including increased post-traumatic stress symptoms, anxiety, depression, helplessness, and risky behaviors (107)(108)(109)(110)(111)(112)(113). The overall rates of depression and anxiety are higher during COVID-19 than prior 16 UNESCO.…”
Section: Role Of the Covid-19 Pandemicmentioning
confidence: 99%
“…A Brunet, M Rivest-Beauregard, M Lonergan, S Cipolletta, A Rasmussen, X Meng, N Jaafari, S Romero, J Superka, AD Brown, et al [31] conducted a survey to investigate PTSD during the COVID-19 pandemic across countries, which indicated few participants met the clinical threshold for PTSD; accordingly, these authors noted that PTSD was not a common symptom associated with the COVID-19 pandemic. On the other hand, some studies concerning China, the Philippines, northern Iran, Poland, and Italy found high levels of PTSD symptoms during the pandemic [32][33][34][35][36][37]. According to the American Psychiatric Association [38],…”
Section: Changes Levels Of Depressive and Ptsd Symptomsmentioning
confidence: 99%
“…The emergence of β-CoVs (SARS-CoV in 2002 and MERS-CoV in 2012) demonstrated the emerging possibility of new pathogenic CoVs in humans via zoonotic transmission ( 1 , 2 ). The pathogenic CoV, SARS-CoV-2, causes coronavirus disease 2019 (COVID-19), first reported in Wuhan, China, in late 2019, resulting in severe global public health issues and substantial economic losses ( 3 5 ). Bats act as a reservoir for CoVs; therefore, it is speculated that the SARS-CoV-2 originated in horseshoe bats before transmitting to humans via an unknown intermediate host ( 6 ).…”
Section: Introductionmentioning
confidence: 99%